Financial imbalances and financial fragility - Frédéric Boissay (European Central Bank (ECB), 2011)
This paper develops a general equilibrium model to analyze the link between financial imbalances and financial crises. The model features an interbank market subject to frictions and where two equilibria may (co-)exist. The normal times equilibrium is characterized by a deep market with highly leveraged banks. The crisis times equilibrium is characterized by bank deleveraging, a market run, and a liquidity trap. Crises occur when there is too much liquidity (savings) in the economy with respect to the number of (safe) investment opportunities. In effect, the economy is shown to have a limited liquidity absorption capacity, which depends —inter alia— on the productivity of the real sector, the ultimate borrower. I extend the model in order to analyze the effects of financial integration of an emerging and a developed country. I find results in line with the recent literature on global imbalances. Financial integration permits a more efficient allocation of savings worldwide in normal times. It also implies a current account deficit for the developed country. The current account deficit makes financial crises more likely when it exceeds the liquidity absorption capacity of the developed country. Thus, under some conditions —which this paper spells out— financial integration of emerging countries may increase the fragility of the international financial system. Implications of financial integration and global imbalances in terms of output, wealth distribution, welfare, and policy interventions are also discussed.
Keywords: E21; F36; G01; G21; 330; Asymmetric information; financial crisis; financial integration; global imbalances; Moral Hazard